Trans-Atlantic data privacy relations as a challenge for democracy / edited by Dan Jerker B. Svantesson, Dariusz Kloza. - Svantesson, Dan Jerker B.; Kloza, Dariusz (European integration and democracy series ;, 2017)
I think you are misunderstanding the perceived problem here, Mr President. No one is saying that you broke any laws. We are just saying it is a little bit weird that you did not have to.' - John Oliver The Daily Show, 10 June 2013 'John Oliver formulated in this context the very question about the limits, about the use and abuse, of the law and of the state's power when it comes to global mass surveillance practices. Where does lie the 'thin red line' between the two legitimate yet seemingly competing interests: national security and privacy? [...] The result we present to the reader might seem merely another book about the Snowden affaire and the fall of Safe Harbor, but these two have been (only) an inspiration. Our object of interest is the protection of data privacy in relations between Europe and Americas as a challenge for democracy, the rule of law and fundamental rights. [...] The present book is very clearly an anthology - it is a compilation of diverse contributions, from different perspectives, within a broad topic. Our aim with this volume is to highlight a selection of particularly 'hot' questions within the topic of trans-Atlantic data privacy relations as they look at the end of 2016. [...] In the final chapter, we draw out and highlight those themes we see emerging within the body of this work. We eventually attempt to suggest a few lessons de lege ferenda. - from the Preface by the editors 'Under the 'Lisbon Treaties', which are in force since 2009, the European Union regards itself as a distinct political entity, which is not a federation of Member States, but it is held together - as Luuk van Middelaar says - with a unique invisible glue". This connection is grounded with shared goals. One of them - expressed both in the Treaty on the Functioning of the European Union (Article 16) and in the Charter of Fundamental Rights of the European Union (Articles 7 and 8) is a unique obligation to protect personal data. Stating that everyone has the right to the protection of personal data concerning them the European Union feels obliged to observe how safe is the data both held in its territory and transferred outside thereof' - from the Foreword by Wojciech R. Wiewiórowski Assistant European Data Protection Supervisor 'Privacy and data protection are topics of international significance. While the EU-US relationship gets a great deal of attention there are also many crucial issues of a more global nature. This book includes contributors of international stature who deal with Snowden and Safe Harbour but also go beyond them to address some of the key topics affecting privacy at the international level. The topics are timely and the authors highly qualified and the book will be of interest to anyone interested in privacy and data protection law and policy.' - Dr Christopher Kuner Co-Director Brussels Privacy Hub Vrije Universiteit Brussel editor-in-chief International Data Privacy Law